Fuel price elasticities for single-unit truck operations in the United States. (July 2015) - Winebrake, James J.; Green, Erin H.; Comer, Bryan; Li, Chi; Froman, Sarah; Shelby, Michael
Highlights: We estimate fuel price elasticities for single-unit trucks in the US between 1980 and 2012. We apply an econometric approach using national transportation datasets. Fuel price elasticities are shown to be inelastic. The results have implications for understanding trucking responses to fuel prices changes. Abstract: This paper provides fuel price elasticity estimates for single-unit truck activity, where single-unit trucks are defined as vehicles on a single frame with either (1) at least two axles and six tires; or (2) a gross vehicle weight greater than 10, 000 lb. Using data from 1980 to 2012, this paper applies first-difference and error correction models and finds that single-unit truck activity is sensitive to certain macroeconomic and infrastructure factors (gross domestic product, lane miles expansion, and housing construction), but is not sensitive to diesel fuel prices. These results suggest that fuel price elasticities of single unit truck activity are inelastic. These results may be used by policymakers in considering policies that have a direct impact on fuel prices, or policies whose effects may be equivalent to fuel price adjustments.